The Role of 'Sense of Place' in the Revitalisation of Heritage Street: George Town, Penang, Malaysia. (December 2021) - Bakri, Aidatul Fadzlin; Robinson, Mike; Samadi, Zalina; Jørgensen, Helle
No abstract available